Tuberculosis survey of free-ranging marsh deer (Blastocerus dichotomus) in Brazil - Luna, Janaina O.; Santos, Manoel A. A.; Durigon, Edison L.; Araújo, João P. [UNESP]; Duarte, José M. B. [UNESP] (American Association of Zoo Veterinarians, 2003)
Esophageal-pharyngeal fluids from 53 free-ranging marsh deer (Blastocerus dichotomus) captured for a research program in the state of Mato Grosso do Sul, Brazil, were assayed for tuberculosis. Total DNA was extracted, amplified by polymerase chain reaction using specific primers for Mycobacterium tuberculosis complex (M. tuberculosis, M. bovis, M. microti, and M. africanum), and observed by agarose gel electrophoresis stained with ethidium bromide. All samples were negative. This, along with necropsy and histopathology data, suggests that these animals are not shedding and probably do not have active disease.
Keywords: Blastocerus dichotomus; Marsh deer; Mycobacterium bovis; PCR; Tuberculosis; bacterial DNA; animal; animal disease; Brazil; deer; genetics; isolation and purification; methodology; microbiology; Mycobacterium; polymerase chain reaction; tuberculosis; wild animal; Animals; Animals, Wild; Deer; DNA, Bacterial; Polymerase Chain Reaction; Animalia; Bacteria (microorganisms); Caesalpinia ciliata; Cervidae; Mycobacterium africanum; Mycobacterium microti; Mycobacterium tuberculosis